1986
DOI: 10.1113/jphysiol.1986.sp016271
|View full text |Cite
|
Sign up to set email alerts
|

Immediate ventilatory response to sudden changes in venous return in humans.

Abstract: 4. In five subjects, elevation of the legs at 30 deg head-up tilt caused a rise in both cardiac output and ventilation, but in two subjects neither occurred. In all seven subjects there was a transient increase in cardiac output and ventilation when the legs were lowered. Ventilation and cardiac output changes were approximately in phase.5. We were therefore unable to dissociate entirely increasing cardiac output from increasing ventilation. The relation between them was certainly not a simple proportional one. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This is the potential of cardiodynamic 'distortion' of the Vm,O 2 kinetics on reaching the lung (Barstow et al 1990 Whipp, 1994). The normal situation, where Q does increase at the onset of exercise (Cummin et al 1986), may confound any comparison of ô Vp,O 2 and ôPCr. The fall of [PCr] to a new steady-state level is expected to begin at the onset of exercise, but the blood flow associated with that fall also changes with its own kinetic response to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This is the potential of cardiodynamic 'distortion' of the Vm,O 2 kinetics on reaching the lung (Barstow et al 1990 Whipp, 1994). The normal situation, where Q does increase at the onset of exercise (Cummin et al 1986), may confound any comparison of ô Vp,O 2 and ôPCr. The fall of [PCr] to a new steady-state level is expected to begin at the onset of exercise, but the blood flow associated with that fall also changes with its own kinetic response to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In seven matched pairs showing no fall in PET, C02 with EEL, the increase in 1I was disproportionately greater than the increase in Q. These results, unlike those of Cummin, Iyawe, Mehta & Saunders (1983), do not support the concept of a simple proportional relationship of Q as a 'driving function' to 1I (Wasserman, Whipp & Castagna, 1974) It has been shown that tonic activity in the expiratory muscles may develop in different experimental conditions in which rhythmic inspiratory activity is greatly reduced or completely abolished (Bainton, Kirkwood & Sears, 1978;Budzin'ska, Euler, Pantaleo & Yamamoto, 1984). Strong inhibitory effects on inspiratory activity are known to be exerted by superior laryngeal nerve (SLN) afferents; however, scanty knowledge is available on their effects on expiratory activity.…”
Section: University DI Milano Italymentioning
confidence: 56%
“…The mechanism(s) by which PASG increase or maintain blood pressure remain a topic of debate. Generally, PASG are thought to cause redistribution of blood volume centrally, leading to increased cardiac filling (Hanke et al 1985; Cummin et al 1986; McSwain, 1988; Bain et al 1989; Geelen et al 1992; Hopman et al 1992). Also, PASG inflation reduces vascular compliance, thus increasing cardiac afterload and systemic vascular resistance (Gaffney et al 1981; Julius et al 1982; McSwain, 1988; Rubal et al 1989).…”
Section: Introductionmentioning
confidence: 99%